Impact of pharmacotherapy follow-up in patients with bronchial asthma in “Boticas y Salud” of Comas District - Lima - Juárez, José R. (2019)
The objective of this research was to measure the impact of pharmacotherapeutic follow-up, in relation to the technique in the use of inhalation medications in ambulatory patients with bronchial asthma, as well as to educate the patient about the characteristics of their disease. We worked with seven patients in a period of five months; in which, through pharmaceuti-cal intervention, they were evaluated in the inhalation technique and in the knowledge about their disease. A registry was made of the MRPs identified, their causes and consequences, as well as the intervention of the pharmacist to resolve them and the results of the intervention. Because of the evaluation of the inhalation technique in the patients, it was found that there was error in the technique in 63.35% of the patients, before the intervention, which was reduced to 28.57% after the same. Regarding the patient’s knowledge about his illness, at the beginning of the program, it was found that only 29.29% of the patients knew about their illness; but after the intervention of the pharmacist, it reached 65%. Only five MRPs were identified in three patients, which were solved 60% (3 of 5): educating patients in 80% (4 of 5) and referring the patient to the doctor in 20% (1 of 5), 20% (1 of 5) was partially resolved and 20% (1 of 5) was not resolved. It ́s concluded that the pharmacotherapeutic follow-up improved the inhalation technique and the knowledge of the disease in the patients of the study.